TALENT MANAGEMENT AND ORGANIZATIONAL PERFORMANCE IN OMAN GOVERNMENT HOSPITALS - Khalood Farzah; Nor Azilah Husin (International Journal of Accounting, Finance and Business, 2022)
Effective talent management requires an understanding of what core talent means,and how to leverage the talent in a manner that allows management to act decisively to drivecompetitive advantage as well as to secure the future success and sustainability oforganisations. Research in healthcare setting in Oman reported non- punitive response toerrors, inadequate staffing and hand offs and transition as areas of healthcare that requireimprovement in Oman. Given their engagement through talent management and greatleadership is critical to improving morale and strengthening Oman healthcare professionalsfor optimum performance of healthcare system. Despite numerous studies on the topic so farlittle attention has been paid to talent management and the role of leadership in public hospitalssetting. The aim of this research is to integrate elements from the individual, organisationaland societal levels to gain a more comprehensive understanding of interactive relationshipbetween talent management, healthcare professionals’ engagement and performance in OmanGovernment Hospitals. The study will contribute to the literature that exists on the concepts ofthis study, namely, talent management, employee engagement, leadership and hospitalperformance. The study seeks to benefit the hospital administrators particularly hospitalmanagement and government of Oman in general. A cross-sectional study among respondentsfrom Sultan Qaboos Hospital Salalah and West Salalah Health Centre will be adequate as agood sample to conduct this study. A questionnaire containing four sections will be used tomeasure the variables in this study from healthcare professionals; points of view. A pre-testanalysis will be carried out on 30 nurses in health centre in Salalah, not included in the sampleof the study, to test the tool practicality and applicability. The data gathered will be analysedin AMOS software for structural equation modelling and the results will be disseminated.